Management challenges for the 21st century - Drucker, Peter F. (Peter Ferdinand), 1909- (New York : HarperBusiness, 1999)
In his first major new book since Post-Capitalist Society, Peter F. Drucker discusses the new paradigms of management - how they have changed and will continue to change our basic assumptions about the practices and principles of management. Drucker analyzes the new realities of strategy, shows how to be a leader in periods of change, and explains "the New Information Revolution," discussing the information an executive needs and the information an executive owes. He also examines knowledge worker productivity, and shows that changes in the basic attitude of individuals and organizations as well as structural changes in work itself are needed for increased productivity. Finally, Drucker addresses the ultimate challenge of managing yourself while still meeting the demands on the individual during a longer working life and in an ever-changing workplace.
Introduction: Tomorrow's "Hot" Issues -- 1. Management's New Paradigms -- 2. Strategy - The New Certainties -- 3. The Change Leader -- 4. Information Challenges -- 5. Knowledge-Worker Productivity -- 6. Managing Oneself.
Includes index.
Keywords: Management -- Forecasting; Twenty-first century -- Forecasts; Management; Organizational change; Knowledge management; Reengineering (Management); Business forecasting